2009
DOI: 10.1242/jeb.023929
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of benthic suction feeding in Callichthyidae and Mochokidae,with functional implications for the evolution of food scraping in catfishes

Abstract: SUMMARYFood scraping has independently evolved twice from suction feeding in the evolution of catfishes: within neotropical Loricarioidea and paleotropical Mochokidae. To gain insight in the evolutionary transitions associated with the evolution towards scraping, we analyzed prey capture kinematics in two species of benthic suction feeders which belong to taxa that are closely related to the scraper lineages (respectively, Corydoras splendens and Synodontis multipunctatus), and compared it to prey capture in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The volume of the buccal cavity was approximated using a series of elliptical cylinders as proposed by Drost and Van den Boogaart [50] (see also [51], [52]). We measured the width and height of the buccal cavity, which equal the major and minor axis of these ellipses, at 100 equally spaced intervals.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of the buccal cavity was approximated using a series of elliptical cylinders as proposed by Drost and Van den Boogaart [50] (see also [51], [52]). We measured the width and height of the buccal cavity, which equal the major and minor axis of these ellipses, at 100 equally spaced intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Kinematic data from standard external view videos suggest that some species may rely predominantly on either dorsal or ventral expansion, rather than using both (e.g. Van Wassenbergh et al, 2009). The contribution of lateral expansion is unknown for many species, but probably also varies interspecifically.…”
Section: Rostrocaudal Extent Of Axial Muscle Shorteningmentioning
confidence: 99%
“…In another example of the coopting of a motor behavior from one function to another, trap-jaw ants typically use the rapid closing strikes of their mandibles for prey capture, but can also use them to propel themselves into the air by simply reorienting strikes to be directed against the ground [22]. In a closer parallel to the gobiid fish system, previous studies have shown herbivorous benthic scraping abilities [25], [26] as well as station-holding abilities [27] among species of catfishes; however it is unclear how closely patterns of movement compare in such cases.…”
Section: Introductionmentioning
confidence: 99%